Pengaruh fasilitas dan motovasi terhadap efektifitas belajar mahasiswa: Fasilitas dan motivasi - Liza, Liza; Nurhakim, Lukman; Trisno, Trisno (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Education as the foundation for shaping high-quality and competitive human resources requires the effectiveness of student learning as the primary focus. Factors influencing learning effectiveness, particularly facilities and motivation, are a serious concern in the context of globalization and rapid changes. Facilities play a crucial role in creating a conducive learning environment. The availability of comfortable classrooms, comprehensive libraries, laboratories, and information technology plays a crucial role in shaping students' abilities. Motivation, as an internal driving force, is key to achieving academic goals. High motivation helps foster independent learning, perseverance, and the spirit to overcome challenges. This research employs a qualitative approach with a literature review method, exploring scholarly works through the Publish or Perish application. The research focuses on the influence of facilities and motivation on student learning. The study reveals a significant correlation between facilities and motivation with the effectiveness of student learning. A conducive learning environment influences students' activity and learning effectiveness. Adequate facilities, such as comprehensive libraries and information technology, enhance the comfort of learning. High motivation supports optimal utilization of facilities. Good integration between facilities and motivation can create a learning ecosystem that supports students' academic growth. Universities and educational institutions need to improve facilities and design effective motivation programs to provide a better learning experience. This conclusion provides guidance for improving the education system and forming a generation ready to face future challenges